Natural bioactive compounds targeting DNA methyltransferase enzymes in cancer: Mechanisms insights and efficiencies - Aanniz, Tarik; Bouyahya, Abdelhakim; Balahbib, Abdelaali; El Kadri, Kawtar; Khalid, Asaad; Makeen, Hafiz A; Alhazmi, Hassan A; El Omari, Nasreddine; Zaid, Younes; Wong, Rebecca Shin-Yee *; Yeo, Chien Ing *; Goh, Bey Hing *; et al. (Elsevier, 2024)
The regulation of gene expression is fundamental to health and life and is essentially carried out at the promoter region of the DNA of each gene. Depending on the molecular context, this region may be accessible or non-accessible (possibility of integration of RNA polymerase or not at this region). Among enzymes that control this process, DNA methyltransferase enzymes (DNMTs), are responsible for DNA demethylation at the CpG islands, particularly at the promoter regions, to regulate transcription. The aberrant activity of these enzymes, i.e. their abnormal expression or activity, can result in the repression or overactivation of gene expression. Consequently, this can generate cellular dysregulation leading to instability and tumor development. Several reports highlighted the involvement of DNMTs in human cancers. The inhibition or activation of DNMTs is a promising therapeutic approach in many human cancers. In the present work, we provide a comprehensive and critical summary of natural bioactive molecules as primary inhibitors of DNMTs in human cancers. The active compounds hold the potential to be developed as anti-cancer epidrugs targeting DNMTs.